Reproduction Management of Buffalo (Bubalus Bubalis) In People's Livestock In Tanjung Lolo District, Sijunjung Regency: Pengelolaan Reproduksi Kerbau (Bubalus Bubalis) Pada Peternakan Rakyat Di Kenagarian Tanjuang Lolo, Kabupaten Sijunjung - Rini Elisia; Fadilla Meidita; Maiyontoni; Taufiqqurrahman (KPN Kopertis X, 2023)
Sijunjung Regency is one of the centers for the development of buffalo livestock in West Sumatra. Even though the buffalo population in this area is quite large, from year to year the population increase is not as expected. One reason is the management of livestock reproduction which is not well controlled by breeders. This community service activity (CSA) for the buffalo livestock group aims to: change the behavior of farmers regarding the reproduction of buffalo livestock by providing knowledge about reproduction management, especially regarding puberty, detection of lust, and artificial insemination programs in buffalo livestock. The program targets are buffalo breeders in Nagari Tanjung Lolo, Tanjung Gadang District, Sijunjung Regency. The approach method used is counseling with a lecture approach and direct demonstrations. In addition, to determine the state of reproduction (ovaries) of buffalo cattle palpation is carried out. Guidance and coaching for breeders is carried out periodically through coordination with one of the breeders in the group. The mentoring activities carried out involved students of the animal husbandry study program. The results of the community service program activities are: 1) breeders know the age of puberty and signs of lust in buffalo cattle. 2) breeders know the reproductive condition (ovaries) of their livestock, 3) breeders know the ideal body condition of a livestock, 4) vitamin E administration to improve the growth and body condition of livestock.